Hemotropic mycoplasmas (hemoplasmas) in wild boars, hunting dogs, and hunters from two Brazilian regions - Fernandes, Asia Janelle (2021)
Haemotropic mycoplasmas (haemoplasmas) are small pleomorphic bacteria infecting erythrocytes of several mammalian species, including human beings. No study to date has focused on the risk of bacteria exposure in hunting activities, particularly in natural environments of highly tick-infested areas. Accordingly, the present study aimed to assess haemoplasma occurrence in the complex encompassing wild boars, hunting dogs and hunters of Brazil. A total of 38/65 (58.5%) wild boars and 94/159 (59.1%) dogs were positive by qPCR for at least one haemoplasma. All 25 hunters were negative. Dogs with high hunting frequency were 2.4 more likely to be infected. Sequencing revealed a probable novel haemoplasma species in wild boars. Although exposure to haemoplasma species was present, the study herein found no evidence of cross-species transmission.